2012
DOI: 10.1002/adsc.201100711
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Olefin‐Oxazoline Ligands (OlefOx) by Rhodium(III)‐Catalyzed Oxidative Olefination

Abstract: The rhodiumA C H T U N G T R E N N U N G (III)-catalyzed oxidative olefination of 2-aryloxazolines is described and has been employed for the synthesis of olefin-oxazoline ligands (OlefOx). The highly modular synthesis starting from readily available 2-aryloxazolines can be performed under an atmosphere of air as the terminal oxidant with catalytic amounts of copper(II)acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 137 publications
0
10
0
1
Order By: Relevance
“…7 Liu and co‐workers,7a as well as Feng and Loh,7b showed that this catalyst system can also be transferred to phenyl carbamates by using overstoichiometric amounts of Cu(OAc) 2 . As independently shown by several research groups, the oxidative Heck reaction can also be conducted with other substrate classes by using Rh6a, 7c,d or Ru catalysts8, 9 in combination with different amounts of Cu(OAc) 2 .…”
Section: Methodsmentioning
confidence: 99%
“…7 Liu and co‐workers,7a as well as Feng and Loh,7b showed that this catalyst system can also be transferred to phenyl carbamates by using overstoichiometric amounts of Cu(OAc) 2 . As independently shown by several research groups, the oxidative Heck reaction can also be conducted with other substrate classes by using Rh6a, 7c,d or Ru catalysts8, 9 in combination with different amounts of Cu(OAc) 2 .…”
Section: Methodsmentioning
confidence: 99%
“…With 2-phenyloxazolines [145] and phenyltriazenes [146] as the substrates, their alkenylations also proceed in the presence of rhodium compounds, as shown in Equations (3. Other reactions are acylation [148], amination [149], halogenation [150] and silylation [151], as shown in Equations (3.3.5)-(3.3.8), respectively.…”
Section: Recent Applications Of Cyclometalation Five-membered Ring Inmentioning
confidence: 99%
“…sowie Feng und Loh7b zeigten, dass dieses Katalysesystem auch auf Phenylcarbamate mit überstöchiometrischen Mengen Cu(OAc) 2 übertragbar ist. Wie mehrere Arbeitskreise unabhängig voneinander nachgewiesen haben, ist die oxidative Heck‐Reaktion bei Verwendung eines Rh‐6a, 7c,d oder Ru‐Katalysators8, 9 und unterschiedlicher Mengen Cu(OAc) 2 auch mit anderen Substratklassen möglich.…”
Section: Methodsunclassified